Introduction of multiple video recording and browsing system into weightlifting training camp - Shirai, K.; Yoshikawa, F.; Kitahara, I.; Ohta, Y.; Kikuta, M. (International Journal of Computer Science in Sport, 2002)
Recently such techniques have been researched and developed that an observer can obtain multiple videos being have simultaneously recorded from several different viewpoints and then can browse one or some synchronized videos from the desirable viewpoint in a real time via broadband network[l,2]. By introducing some components into sporting facilities that are available in the techniques having been utilized or developed in the previous researches, we make an attempt to develop a system that can provide instant visual feedback from multiple viewpoints to athletes and coaches.This report summarizes a prototype Multiple Video Recording and Browsing System that we have been developing, and then describes an example of instant visual feedback activities for weightlifter that were carried out by using this prototype system.